La contaminación por ozono troposférico. El caso de Motril (Granada) - Velázquez de Castro González, Federico; Jiménez Arcas, Sara (Observatorio Medioambiental, 2007)
The photochemical pollution, where the ozone is the most representative compound, is the outstanding concern in the Spanish environmental profile, because it overcomes the estabished European and National values. Andalucía, in the Spanish Southern, undergoes high levels of temperature and solar radiation, especially in summer. Industrial areas (either Cádiz or Huelva) are very sensitive to the atmospherical pollution, but other places, like Motril in Granada, shows high ozone values too. The reasons are the primary pollutants emissions (because of the strong traffic levels in touristic areas), but especially as consequence of the meteorological aspects, as the breeze sistems of the Mediterranean sea or the East wids that brings to Motril the emitted polutants along the Mediterranean coast. This situation have to be researched in order to know how is affecting to the health and agriculture